1994
DOI: 10.1111/j.1365-4362.1994.tb01540.x
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic Acid in Cutaneous Intrinsic Aging

Abstract: We propose that the variations of the levels of hyaluronic acid in the dermis in aging could account for some of the most striking alterations of the aged skin, including decreased turgidity, less support for microvessels, wrinkling, and altered elasticity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
129
0
6

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 190 publications
(139 citation statements)
references
References 8 publications
1
129
0
6
Order By: Relevance
“…In addition analysis of skin biopsies from chronically sun-exposed versus sun-protected areas of human skin revealed loss of HA as well. [51][52][53] In summary, the current data demonstrate that chronic, repetitive UVB irradiation induces loss of HA from murine dermis because of transcriptional down-regulation of HAS1, HAS2, and HAS3. The underlying mechanism might involve decreased transcriptional activation of HAS expression through TGF-␤1-dependent pathways.…”
Section: Discussionmentioning
confidence: 98%
“…In addition analysis of skin biopsies from chronically sun-exposed versus sun-protected areas of human skin revealed loss of HA as well. [51][52][53] In summary, the current data demonstrate that chronic, repetitive UVB irradiation induces loss of HA from murine dermis because of transcriptional down-regulation of HAS1, HAS2, and HAS3. The underlying mechanism might involve decreased transcriptional activation of HAS expression through TGF-␤1-dependent pathways.…”
Section: Discussionmentioning
confidence: 98%
“…These compounds render normal skin plump, soft and hydrated, and are believed to assist in maintaining proper salt and water balance. Several studies suggest that GAGs, particularly HA, have been found to be reduced in amount in photo-aged skin [67]. Some studies offer conflicting reports, however, suggesting no changes in the level of GAGs in aged skin [68].…”
Section: Glycosaminoglycans (Gags)mentioning
confidence: 96%
“…The acquired images were used to extract information concerning the following parameters taken as indices of aging: collagen fibres, and amorphous component. In fact, the aging process affects the two parameters listed above as follows: collagen fibres increase in thickness and density, amorphous component (mainly composed by hyaluronic acid and glycosaminoglycans) decreases, hence limiting tissue hydration [57]. In the acquired images, collagen can be directly visualized using SHG microscopy, while the abundance of the amorphous component can be indirectly inferred in terms of increased tissue scattering and hence reduced image contrast.…”
Section: Visual Examination Of Shg Imagesmentioning
confidence: 99%